Implementasi Undang-Undang Cipta Kerja Dalam Perjanjian Kerja Waktu Tertentu Di Masyarakat (Perspektif Undang-Undang Nomor 6 Tahun 2023 Tentang Cipta Kerja) - Ahmad Akbar Rudin (PSHPM Untag Semarang, 2026)
Fixed-term employment agreements (PKWT) are a policy that is inseparable from the Job Creation Law. This study discusses the implementation of fixed-term employment agreements in society. The article evaluates the impact of the Job Creation Law on PKWT by analyzing changes in legal provisions that affect the characteristics, rights, and protections of workers. The method used in this study employs a descriptive approach; qualitative descriptive research can be understood as a series of activities related to analyzing events, phenomena, or conditions socially. This type of research is qualitative research. This study discusses obstacles such as mismatched worker qualifications, lack of understanding of employment contracts, lack of knowledge about labor laws, and insufficient understanding of government regulations related to fixed-term employment agreements (PKWT). Therefore, efforts are needed to improve understanding and compliance in the implementation of PKWT to create a fairer working environment.